FACTORS RELATED TO COMPLIANCE DIET FOR CHRONIC KIDNEY FAILURE PATIENTS UNDERGOING HEMODIALYSIS AT PATI ISLAMIC HOSPITAL - Nining Rokhyati; Feri Catur Yuliani; Rizal Fajri; Akbar Amin Abdullah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Chronic kidney failure (CKD) is a condition characterized by progressive and irreversible decline in kidney function. One of the main therapies for CKD patients is hemodialysis, which requires adherence to a special diet to prevent complications and maintain quality of life. This study aims to analyze the relationship between age, gender, education level, length of hemodialysis, knowledge level, and family support with dietary compliance in CKD patients undergoing hemodialysis at RSI Pati. This study used a quantitative method with a cross-sectional design with a total sampling technique, involving 50 respondents who met the inclusion criteria. The instrument used was a questionnaire on respondent characteristics, knowledge, family support, and dietary compliance. Data analysis was carried out univariately and bivariately using the Chi-Square test. The results showed that the variable that had a significant relationship with dietary compliance was the level of knowledge (p = 0.011). Meanwhile, age (p = 0.386), gender (p = 0.248), education level (p = 0.071), duration of hemodialysis (p = 0.137), and family support (p = 0.498) did not show a significant relationship. Dietary compliance in patients with chronic kidney disease (CKD) undergoing hemodialysis is largely influenced by their level of knowledge. It is recommended that healthcare professionals develop structured and ongoing educational programs, tailored to patient needs, to improve dietary compliance.